Financial strain, inflammatory factors, and haemoglobin A1c levels in African American women. (18th October 2014) - Cutrona, Carolyn E.; Abraham, William T.; Russell, Daniel W.; Beach, Steven R. H.; Gibbons, Frederick X.; Gerrard, Meg; Monick, Martha; Philibert, Robert
<x xml:space="preserve">Abstract</x> Objective Type 2 diabetes disproportionately affects African American women, a population exposed to high levels of stress, including financial strain (Centers for Disease Control & Prevention, 2011, http://www.cdc.gov/diabetes/pubs/pdf/ndfs_2011.pdf). We tested a mediational model in which chronic financial strain among African American women contributes to elevated serum inflammation markers, which, in turn, lead to increased haemoglobin A1C (HbA1c) levels and risk for type 2 diabetes. Methods We assessed level of financial strain four times over a 10‐year period and tested its effect on two serum inflammation markers, C‐reactive protein (CRP) and soluble interleukin‐6 receptor (sIL‐6R) in year 11 of the study. We tested the inflammation markers as mediators in the association between chronic financial strain and HbA1c, an index of average blood glucose level over several months. Design Data were from 312 non‐diabetic African American women from the Family and Community Health Study (FACHS; Cutrona et al., 2000, J. Pers. Soc. Psychol., 79, 1088). Results Chronic financial strain predicted circulating sIL‐6R after controlling for age, BMI, health behaviours, and physical health measures. In turn, sIL‐6R significantly predicted HbA1c levels. The path between chronic financial strain and HbA1c was significantly mediated by sIL‐6R. Contrary to prediction, CRP was not predicted by chronic financial strain. Conclusions Results support the role of inflammatory factors in mediating the effects of psychosocial stressors on risk for type 2 diabetes. Findings have implications for interventions that boost economic security and foster effective coping as well as medical interventions that reduce serum inflammation to prevent the onset of type 2 diabetes. <boxed-text content-type="box" id="bjhp12120-blkfxd-0001" position="anchor" orientation="portrait"> Statement of contribution What is already known on this subject? Financial strain is a risk factor for many disorders, and it is associated with inflammation in the peripheral bloodstream. Inflammation processes are known to be associated with insulin resistance, a risk factor for type 2 diabetes mellitus. What does this study add? Financial strain, a psychological stressor, predicts higher levels of an inflammatory marker, sIL‐6r, when controlling for a set of known predictors of inflammation. This inflammatory marker, in turn, predicts haemoglobin A1C level, a marker of risk for diabetes. The association between financial strain, a psychological stressor, and hemoglobin A1C is mediated by the inflammatory marker, sIL‐6r, suggesting that one mechanism through which psychological stressors increase risk for diabetes is through inflammatory mechanisms. </boxed-text>